Application of the Discovery Learning Learning Model Assisted by the Wordwall Games Application to Improve the Learning Outcomes of Class X-2 Students at SMAN Madani Integrated Model Palu - Nurhidjra, Nurhidjra; Etta, Nita Suryani; Jamaludin, Jamaludin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The aim of this research is to improve the learning outcomes of class This research is class action research (Class Action Research) which consists of two cycles. Each cycle consists of action planning, action implementation, evaluation (observation) and reflection. The research subjects were students of class Data sources come from teachers and students obtained through observation, interviews, tests and document review. The data analysis technique used is descriptive analysis. The results of the research show that: (1) The teacher's ability to carry out learning using the discovery learning method assisted by the wordwall games application to improve student learning outcomes in Civics learning in class X-2 in cycle I had an average of 56.81%, while in cycle II to 86.36%, this shows an increase of 29.55%. (2) There was an increase in student learning outcomes in Civics learning using the discovery learning method assisted by the wordwall games application in class %, in cycle II it was 80.6% with a completion percentage of 91.42%, this shows an increase in student learning outcomes of 7.6%.